Influence of paeoniflorin and menthol on puerarin transport across MDCK and MDCK‐MDR1 cells as blood–brain barrier in vitro model. (13th December 2017) - Yang, Bing; Du, Shouying; Lu, Yang; Jia, Shan; Zhao, Mengdi; Bai, Jie; Li, Pengyue; Wu, Huichao
Abstract: Objective: Our objective of this research was (1) to investigate the transport characteristics of puerarin through MDCK‐MDR1 and MDCK cells and (2) to evaluate the effects of paeoniflorin and menthol on puerarin transport so as to (3) explore the enhancement mechanism. Methods: The cytotoxicity of drugs on MDCK and MDCK‐MDR1 was evaluated by the MTT assay, and the transport studies were performed in both directions. The membrane fluidity was evaluated by fluorescence recovery after photobleaching, and the membrane potential was estimated by the accumulation of DiBAC4(3) in the cells. Key findings: Puerarin showed relatively poor absorption and purely passive diffusion. However, the efflux ratio of puerarin was <2 in MDCK‐MDR1 models, which suggested puerarin was not P‐gp substrates so as to the P‐glycoprotein activity determination of puerarin. With the existence of menthol, the transcellular transport of puerarin increased and puerarin transport significantly increased when co‐administrated with paeoniflorin and menthol. Conclusions: The enhancing effect of paeoniflorin and menthol may be attributed to the significant enhancement on cell membrane fluidity, the decrease in membrane potential. Immunostaining results indicated that menthol behaved as transport enhancer by disassembly effect on tight junction integrity.